Analisis Nilai Perjuangan Tokoh Zainuddin dalam Novel Buya Hamka Tenggelamnya Kapal Van Der Wijk - Damariswara, Rian; Jadmiko, Rahmad Setyo (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The purpose of this study is to analyze the values ​​of the struggle of the Zainuddin character in Buya Hamka's novel Tenggelamnya Kapal Van Der Wijck. . This research directly collects information obtained from the object of research, namely the novel "The Drowning of the Van Der Wijck Ship", trying to get a picture of the struggle of the character Zainuddin. The results of the study are as follows. 1) family struggle, namely Zainuddin trying to find cultural identity from his father and mother. 2) The struggle for love, namely Zainuddin falls in love with her. However, this relationship was opposed by the girl's customs because Zainuddin's culture was not clear, while the girl's family culture highly respected customs. 3) career struggle, namely Zainuddin trying to get up from his sadness. Assisted by his best friend named Muluk. Zainuddin managed to become a successful person by publishing works that poured all of his sorrows into stories.